Trampas de pobreza: Evidencia para las regiones de Argentina - Emilia Millón; Bruno Rodrigo García (Atlantic Review of Economics (ARoEc), 2018)
– The paper search for evidence of poverty traps in different regions of Argentina. The selected methodology is based on the model proposed by Antman and Mckenzie (2005), it suggests a specification for the income's dynamic that allows multiple balances, using the framework of classical growth model. In particular, this paper proposes an extension to that methodology. Using the functional version from Antman and Mckenzie (2005), the result determines the existence of weak poverty traps in 4 of the 6 regions. With the alternative approach, the result wins robustness and gets strong evidence for 4 regions.
Keywords: C23; C81; I32; 330